Growth and Distribution of Agrarian Assets in the Punjab (The Pakistan Development Review, 1991)
This is a micro study of the growth and distribution of non land agrarian assets over time, in two villages of the Punjab. Widespread adoption of the Green Revolution inputs, seed and fertilizer, has generated a high rate of acquisition of agrarian assets, especially tubewells and mechanisation. The HYV enhanced profitability and income should have permitted an equally widespread acquisition of assets. This study uses an exogenous-endogenous model to show two constraints on asset acquisition.